2010
DOI: 10.1091/mbc.e09-09-0756
|View full text |Cite
|
Sign up to set email alerts
|

The Late Endosome is Essential for mTORC1 Signaling

Abstract: Recent work suggests a link between endocytic trafficking and mTORC1 signaling. This paper demonstrates a specific requirement for the integrity of the late endosomal compartment for amino acid and insulin-stimulated mTORC1 signaling to downstream effectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 57 publications
11
128
0
Order By: Relevance
“…PAO-induced mTORC1 Activation Is Independent of RagRagulator System-Translocation of mTORC1 to lysosomes is a critical step for amino acid-induced mTORC1 activation, where Ragulator (MP1⅐p14⅐p18 complex) plays a crucial role in anchoring Rag small GTPases on the lysosomal membrane (11,12,46). Sancak et al (12) showed that amino acid stimulation failed to induce S6K phosphorylation and mTOR translocation to the lysosome in Ragulator-deficient cells.…”
Section: Mtorc1 But Not Mtorc2 Is Activated By Cysteinementioning
confidence: 99%
“…PAO-induced mTORC1 Activation Is Independent of RagRagulator System-Translocation of mTORC1 to lysosomes is a critical step for amino acid-induced mTORC1 activation, where Ragulator (MP1⅐p14⅐p18 complex) plays a crucial role in anchoring Rag small GTPases on the lysosomal membrane (11,12,46). Sancak et al (12) showed that amino acid stimulation failed to induce S6K phosphorylation and mTOR translocation to the lysosome in Ragulator-deficient cells.…”
Section: Mtorc1 But Not Mtorc2 Is Activated By Cysteinementioning
confidence: 99%
“…Kinesin family member (KIF) 2A is one of a handful of kinesins that apparently do not transport cargo, but instead depolymerize microtubules. In HeLa cells, KIF2A was shown to regulate the location of lysosomes in the cytoplasm, which is thought to be essential for mTORC1 activation (15)(16)(17)(18). We find that KIF2A and the closely related kinesin KIF2C (also known as MCAK) also control lysosomal organization in human bronchial epithelial cells.…”
mentioning
confidence: 69%
“…Alternatively, like LRS, SH3BP4 could act as a leucine sensor in different cellular compartments. Amino acids were able to affect cellular localization of mTORC1, which depended on vesicle trafficking proteins (Flinn et al, 2010;Hennig et al, 2006;Li et al, 2010;Sancak et al, 2008). The function of SH3BP4 to regulate vesicular trafficking might be important for mTORC1 regulation in response to amino acids.…”
Section: How Sh3bp4 Function Is Regulatedmentioning
confidence: 99%
“…Vam6p binds to Gtr1p and acts as a guanine nucleotide exchange factor (GEF) for Gtr1p (Binda et al, 2009), thus positively regulating amino acid-TORC1 signaling. In HeLa cells, knockdown of hVps39, the mammalian ortholog of Vam6p, suppressed the activation of mTORC1 by amino acids and insulin (Flinn et al, 2010). Whether the suppression is due to inhibition of Rag GTPases needs further investigation.…”
Section: Vam6p Is a Gef For Gtr1 Gtpasementioning
confidence: 99%